P47 Efficacy and safety of antifungal treatment in fungal asthma; a real life study. (December 2018) - Fleet, S; Mitchell, V; White, L; Bahron, A; Mansur, AH
Abstract : Background: Fungal asthma comprises severe asthma with fungal sensitisation (SAFS) or bronchopulmonary aspergillosis (ABPA). The efficacy and safety of antifungal treatment in this group of patients remained undetermined. Aim: To assess the efficacy and safety of antifungal treatment in fungal asthma in real life settings in a tertiary asthma centre. Methods: This was a retrospective study. Details of all patients attended a tertiary severe asthma centre in England between 2012 to 2018, were reviewed to identify cases meeting the criteria for SAFS and ABPA (ref) and were treated with antifungals (itraconzaole, voriconazole, posaconazole). Clinical outcomes were compared at baseline and 12 months after treatment. Standard statistics were used to compare variables. Results: In total 563 patient records were reviewed of which 80 (14.2%) had fungal asthma that included SAFS (n=59, 10.5%) and ABPA (n=21, 3.7%). Of these 28/80 (36%) had itraconzole (26), voricanozole (1) posaconzole (4) treatments. The mean age of the treated group was 56 years (range 30–79), females=17 (58.6%). Following 12 months treatment compared to baseline we observed a significant decrease in the mean rescue oral corticosteroids (OCS) from 4.31 to 2.25 per annum (p=0.0103), and mean maintenance oral prednisolone from 3.06 mg/day to 1.11 mg/day (p=0.351). There was non-significant decrease in median total immunoglobulin E (IgE) from 520 iu/l to 335 iu/l (p=0.0676). However, there were no significant interval changes in forced expiratory volume in one second (FEV1), asthma control questionnaire (ACQ), fraction exhaled nitric oxide (FeNO), blood eosinophils or IgE specific to Aspergillus. Side effects related to antifungal treatment were recorded in 9 cases (31%); skin rash (1), abnormal liver function test (2), nausea (1), hair loss (1), dizziness (1), sore eyes (1), tendon pain (1), adrenal insufficiency (1) and peripheral oedema (1) 'two patients had >1 side effects'. Conclusion: Only the minority of the fungal asthma patients had antifungal treatment and in this group we observed significant reduction in exacerbations and corticosteroids requirement. The clinical significance of this is uncertain due to confounders prompting the need for adequately powered controlled trials.